Model reference adaptive control with adaptive parametric black box controller - Nasim, Ahmed; Mohd Yusoff, Mashor, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/